If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 + 2x = -39 + 1x Solving -13 + 2x = -39 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -13 + 2x + -1x = -39 + 1x + -1x Combine like terms: 2x + -1x = 1x -13 + 1x = -39 + 1x + -1x Combine like terms: 1x + -1x = 0 -13 + 1x = -39 + 0 -13 + 1x = -39 Add '13' to each side of the equation. -13 + 13 + 1x = -39 + 13 Combine like terms: -13 + 13 = 0 0 + 1x = -39 + 13 1x = -39 + 13 Combine like terms: -39 + 13 = -26 1x = -26 Divide each side by '1'. x = -26 Simplifying x = -26
| 38-3x=-10 | | .5n=n+5 | | -50a/50=54/-50 | | c^2-9c+14= | | -1x=-33 | | f(12)=60-2/3r | | Y=1.8666Ln(x)+90.385 | | 30-2x=9-9x | | 300=25x | | 30x-2x=9-9x | | 6x+-8=16+10x | | 0.3p/-p | | 3-2x+4x+6= | | 25A=5 | | 2x/x-3=9/x-7 | | 5c-4-3c+1=8c+2 | | 5x+3=6x+17 | | 48x+48=0 | | 3x-2=4(x+5) | | 6x+32=16x-8 | | 15y+5=5 | | 2x^2+19xy+24y^2=0 | | 16x^2-4x^4=0 | | 13x+32=16x-48 | | 15+x=1 | | 25x^2-1=10x | | BY=36 | | 7(x+7)=7x+49 | | 9x-(3/2)y=1 | | 1x+40=1x-10 | | (x^2+9)%(x-3) | | 12+3x^2+12x=0 |